The Principle and Foundation in the Ignatian Spiritual Exercises as a Paradigm for a Creational and Ecological Spirituality (Hekima Review, 2015)
Much has been written about the “Spiritual Exercises” of Saint Ignatius of Loyola but the contextualisation of particular meditations or contemplations to current issues has been rather slow. Perhaps this is not so much because it has not taken place but rather that most of it remains in the spiritual realm where only the retreatant and his spiritual director have access under the guidance of the Holy Spirit. This article is an attempt to reflect on the Principle and Foundation in the “Spiritual Exercises” and to examine how it can contribute to a better understanding of creation and the current challenge of maintaining an ecological balance in the universe.